Pragmatics of Speech Acts and Illocutionary Force in YouTube Podcasts: A Linguistic Study of Digital Media Discourse - Neidya Fahma Sunendar; Kevin Andrian Seda (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
The podcast phenomenon is one of the most popular forms of media in today’s digital world. Podcasts serve as a medium of communication in various contexts, such as entertainment, education, and news. In this context, speech acts and the use of politeness strategies play a crucial role in the interaction between guests and hosts. This study examines illocutionary meaning in podcast interactions as a communication strategy. Illocutionary speech acts refer to social actions performed through speech, such as stating, requesting, or promising, which go beyond the literal meaning of the words used (Bach & Harnish, 1979). The method used in this study is a qualitative descriptive method. The data in this study consist of podcasts on the topic of teenage victims of bullying on social media. Analysis of 531 utterances across two podcast episodes revealed that constative acts dominated the guest’s turns (88.36–90%), while directive acts dominated the host’s turns (63.15–73.94%). These findings suggest that podcast hosts heavily rely on asking questions and offering advice to steer emotionally sensitive conversations, thereby offering practical implications for responsible language use in digital media. These findings offer practical implications for podcast content creators to adopt polite and empathetic language strategies in digital media discourse.